COMPUTERIZED SYSTEM ADMINISTRATION PROJECT IN. BITA ENARCON ENGINEERING JAKARTA - Sumariyo Sumariyo; Ir. Aqwam Rosadi K (Jurnal Sistem Informasi, 1996)
In order to increase utilization of penglolaan for Computerized ProjectAdministration System in PT. Bita Engineering Enarcon Jakarta, so we need a gooddata-handling system that provides a fast and accurate information. Becausecomputers can process data quickly in large quantities with high accuracy, it is farmore effective and efficient when compared with the manually.